PSIII-17 The effects of a yeast product on apparent total tract macronutrient digestibility, fecal characteristics, fecal fermentative end products, fecal microbiota, and immune responses of adult dogs. (5th December 2019) - Lin, Ching-Yen; Steelman, Andrew J; Godoy, Maria R C de; Swanson, Kelly S
Abstract: Research in various animal species has demonstrated the effectiveness of yeast products to improve health and performance. However, little research on yeast products are available for dogs. The objective of this study was to investigate the effects of a yeast product on apparent total tract macronutrient digestibility (ATTD), fecal characteristics, fecal microbiota, and immune responses of adult dogs. Twelve adult female beagles (age: 4.8±0.9 yr; BW: 13.3±0.7 kg) were fed the same diet, but supplemented with a yeast product (165 mg/d) or a placebo (125 mg cellulose/d) via gelatin capsules in a crossover design. In each period, a 21-d adaptation phase was followed by 5 d of total fecal collection for ATTD measurement. Fresh fecal samples (within 15 min defecation) were collected on d 22 for fecal dry matter, pH, fermentative end-products, and fecal microbiota measurements. Blood samples were collected on d 27 and peripheral blood mononuclear cells were isolated for evaluations of immune cell populations and immune cell responsiveness. Except for microbiota data, data were analyzed using Mixed Models procedure of SAS 9.4. Microbial sequence data were analyzed using QIIME 1.9.1. and STAMP 2.1.3. ATTD, fecal characteristics and fermentative end-products were not altered by treatment (P > 0.05). Microbial alpha- and beta-diversity and specific microbial taxa were not affected by treatment (P > 0.05). Immune cell populations and immune cell responsiveness of toll-like receptors were not altered by treatment (P > 0.05). However, the strong period effect reported for all parameters may have mitigated the yeast product expected benefits. In conclusion, the yeast product tested in this study did not significantly alter the outcomes measured in healthy adult dogs. Future studies testing higher yeast product dosages, studying dogs undergoing stress, antibiotic administration or immune challenge, or studying dogs most susceptible to gastrointestinal distress (weanling; geriatric), may be of interest.